Design and Testing of a Remote Deployable Water Purification System Powered by Solar Energy - E. Keith, Amber; French, Jesse J. (Advances in Technology Innovation, 2019)
The design of an all-inclusive, self-sufficient, sustainable water purification system for application in developing regions of the world can improve living conditions for people world-wide, especially in regions where access to clean drinking water is limited or unavailable. According to the World Health Organization, the 2015 global census estimated that 663 million people worldwide live without access to safe drinking water sources [1]. An estimated 315,000 children die each year from diarrheal diseases caused by lack of clean water and poor sanitation [2]. Based on these statistics, an all-inclusive, self-sufficient, remote-deployable water purification system has been designed, constructed, and tested to validate the concept of a renewable energy system. The system is integrated into a standard 20-foot shipping container for ease of deployment worldwide. Once situated in the operating area, the shipping container is used as the system shelter and solar panels are mounted to the roof at a location-dependent fixed angle. The solar panels are connected to a battery bank which operates the system. The water purification process utilizes a five-step progression which filters the contaminated freshwater, removing suspended particles and bacteria from the water and purifying the water to the standards of the EPA Safe Drinking Act [3]. Testing verifies the capability of the solar panels to generate enough electricity to power the system and recharge the battery bank. The solar panel array has the rated power output of 2,320 Watts. The water purification operates on a maximum of 97.9 Watts of available power. With the fully charged battery bank, the water purification system can operate for 24-hours without additional solar input. With a freshwater source, the purification system can yield up to 440 liters of water per hour.